2017
DOI: 10.1177/1352458517690269
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brain atrophy rates are associated with lower risk of disability progression in patients with relapsing multiple sclerosis treated with cladribine tablets

Abstract: Background:Neuroimaging studies have used magnetic resonance imaging-derived methods to assess brain volume loss in multiple sclerosis (MS) as a reliable measure of diffuse tissue damage.Methods:In the CLARITY study (ClinicalTrials.gov NCT00213135), the effect of 2 years’ treatment with cladribine tablets on annualized percentage brain volume change (PBVC/y) was evaluated in patients with relapsing MS (RMS).Results:Compared with placebo (–0.70% ± 0.79), PBVC/y was reduced in patients treated with cladribine ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 10 publications
3
50
0
Order By: Relevance
“…Cladribine, an antiproliferative agent that takes effect by interfering with DNA synthesis, has shown significant effects in terms of relapse rate and disability progression [160,161]. Data from CLARITY study suggested that at 18 months, patients treated with cladribine had 20%reduction in brain atrophy compared with patients receiving placebo [162]. However, further studies are needed, in order to cladribine's effect on brain atrophy rates, be fully elucidated [161,163,164].…”
Section: Emerging Dmts and Their Effect On Pbvcmentioning
confidence: 99%
“…Cladribine, an antiproliferative agent that takes effect by interfering with DNA synthesis, has shown significant effects in terms of relapse rate and disability progression [160,161]. Data from CLARITY study suggested that at 18 months, patients treated with cladribine had 20%reduction in brain atrophy compared with patients receiving placebo [162]. However, further studies are needed, in order to cladribine's effect on brain atrophy rates, be fully elucidated [161,163,164].…”
Section: Emerging Dmts and Their Effect On Pbvcmentioning
confidence: 99%
“…An exploratory analysis on the cladribine tablets treating multiple sclerosis orally (CLARITY) study (phase-3, double-blind, placebo-controlled, multicenter trial in patients with RMS assessing the effects of cladribine tablets given annually over 2 years) [117] disclosed that cladribine significantly reduced brain atrophy in comparison with placebo treatment, with residual rates in treated patients being close to the physiological rates [118]. Indeed, compared with placebo (−0.70% ± 0.79), the annualized percentage brain volume change (PBVC/ y) was reduced in patients treated with cladribine tablets 3.5 mg/kg (−0.56% ± 0.68, p = 0.010) and 5.25 mg/kg (−0.57% ± 0.72, p = 0.019).…”
Section: Cladribinementioning
confidence: 99%
“…Cladribine treatment was associated with an increase in the proportion of participants who remained free from Gd-enhancing lesions and new T2 lesions at the end of the 96-week study period 24. There was also a statistically significant reduction in annual brain volume loss in the cladribine treatment groups compared with placebo 25. The positive clinical effects were further underpinned by positive Quality of life data also indicated significant improvement in one out of the two metrics used (EQ-5D) in the cladribine versus placebo groups 26.…”
Section: Introductionmentioning
confidence: 91%